Mortality in people with coeliac disease: Long-term follow-up from a Scottish cohort - Quarpong, Wilhemina (United European Gastroenterol J, 2018)
BACKGROUND: Few studies have determined the very long-term mortality risks in adult and childhood-diagnosed coeliac disease. OBJECTIVE: We quantified mortality risks in coeliac disease and determined whether age at diagnosis, or time following diagnosis, modified these risks. METHODS: Standardised mortality ratios were determined using data from a cohort of 602 coeliac patients assembled between 1979–1983 from Lothian, Scotland, and followed up from 1970–2016. RESULTS: All-cause mortality was 43% higher than in the general population. Excess deaths were primarily from haematological malignancies (standardised mortality ratio, 4.77) and external causes (standardised mortality ratio, 2.62) in adult and childhood-diagnosed cases respectively. Mortality risks declined steadily with time in adult-diagnosed cases (standardised mortality ratio, 4.85 in first year compared to 0.97, 25 years post-diagnosis). Beyond 15 years, this group had a significantly reduced risk of any malignancy (standardised mortality ratio, 0.57 (95% confidence interval: 0.33–0.92)). In contrast, for childhood-diagnosed cases an increased risk existed beyond 25 years (standardised mortality ratio, 2.24). CONCLUSIONS: Adult-diagnosed coeliac patients have a temporarily increased mortality risk mainly from malignant lymphomas and a decreased risk of any malignancy beyond 15 years post-diagnosis. In contrast, childhood-diagnosed cases are at an increased risk of mortality mainly from external causes, and have long-term mortality risks that requires further investigation.